Analisis Tingkat Kepuasan Pengguna Sistem Pembelajaran Daring Menggunakan Metode End User Computing Satisfaction - Rahmah Khairani; Tengku Khairil Ahsyar; Eki Saputra (Forum Kerjasama Pendidikan Tinggi, 2022)
The Online Learning System (SPADA) is a system implemented by STIKes Hang Tuah Pekanbaru to create an effective and productive learning culture. In implementing this system, there are still some problems, such as features that do not work properly, the color of the system display is too simple, there are many submenus in one menu, users feel confused when they run the system for the first time, the data processing process is more time consuming and there are several menus. which has not been updated in a long time. In addition, from the beginning of its implementation until now, there has been no report that can explain how the level of user satisfaction with SPADA at STIKes Hang Tuah Pekanbaru. Therefore, an analysis of the measurement of user satisfaction with SPADA was carried out to determine the level of user satisfaction and make recommendations for improvement in the management of SPADA in the future. The method used is End User Computing Satisfaction or EUCS. This method is based on 5 dimensions, namely Content, Accuracy, Format, Ease Of Use, and Timeliness. The process of collecting data in this study was carried out through interviews, observations and distributing questionnaires to 98 respondents using the Simple Random Sampling technique. The data obtained were calculated using SmartPLS version 3.3. Where in this study the results showed that the level of satisfaction of SPADA users was 70%, which means that users were satisfied using SPADA. Furthermore, related to several problems that users complained about, the researchers gave 6 recommendations for improvements to SPADA which aim to increase SPADA user satisfaction at STIKes Hang Tuah Pekanbaru.